2017
DOI: 10.17265/2159-5526/2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Structural Vector Autoregressive Analysis of Monetary Policy in Thailand

Abstract: This paper highlights the importance of monetary policy transmission mechanism in Thailand since the 1997 financial crisis and then undertakes an empirical investigation of Thailand monetary policy. This study makes effort to address both two aspects of monetary transmission mechanism, namely channels of monetary policy and the effect of monetary policy shocks on key macroeconomic variables. To address these issues, the paper specifies structural vector autoregressive (SVAR) models and estimates them using qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…Following Davoodi (2013), Arwatchanakarn (2017) and Bwire (2019), a standard SVAR is formulated starting with a generalized reduced-form VAR of order p with autoregression denoted below. 1) is transformed as, again we assume the error term to be white noise.…”
Section: Methodology and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Following Davoodi (2013), Arwatchanakarn (2017) and Bwire (2019), a standard SVAR is formulated starting with a generalized reduced-form VAR of order p with autoregression denoted below. 1) is transformed as, again we assume the error term to be white noise.…”
Section: Methodology and Datamentioning
confidence: 99%
“…Interestingly, further findings confirm that three key channels including interest rate, exchange rate and credit were effective in the transmission of the actions of the Central Bank to the Tunisian economy. However, Arwatchanakarn (2017) in his empirical findings revealed that interest rate channel and narrow money were robust in transmitting the actions of monetary authorities to the economy in Thailand. Notwithstanding, exchange rate channel, was however moderately useful in channeling monetary policy effects in the Thai economy.…”
Section: Empirical Literaturementioning
confidence: 98%
“…The SVAR has become more popular than the ordinary VAR, since theoretical and empirical grounds can be incorporated for imposing the restrictions on the model. Christiano et al (1999) for instance, applied the SVAR to examining the effects of monetary policy shocks, and Phiromswad 2015and Arwatchanakarn (2017) also utilized the SVAR for the analyses of Thailand monetary policy.…”
Section: Policy Transmission Effect On Inflationmentioning
confidence: 99%
“…The International Monetary Fund (IMF) defines monetary policy as the main tool in controlling and achieving price stability and for helping maintain economic fluctuations. Monetary policy is the most active tool used for macroeconomic stabilization in countries with independent currencies (Arwatchanakarna, 2017). To do this well, they need to know how changes in policy instruments affect the economy (Cesa-Bianchi, Thwaites and Vicondoa, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism can occur through money, interest rates, credit, exchange rates, and asset price lines. But some economists only focus on one path, is Mishkin (1995) which makes the interest rate channel the standard of monetary policy transmission (Arwatchanakarna, 2017). Of the various channels, price stability remains the main target.…”
Section: Introductionmentioning
confidence: 99%